A Review: Exploring Nutrition Approaches to Improve Mental Health Among Athletes: Focus on Depression and Disordered Eating - Zuzanna Malinowska; Iana-Maria Hadjieva; Julia Majsiak; Joanna Michalina Jurek (Journal of Coaching and Sports Science, 2024)
Elite sports environments can increase psychiatric conditions like stress and depression due to social pressure for specific body shapes, encouraging disordered eating behaviors, especially in endurance, aesthetic, and weight-dependent sports. This review aims to investigate eating habits among athletes suffering from poor mental health and identify dietary strategies or nutritional advice to mitigate these conditions in physically active individuals. The review focused on studies conducted after 2010 involving adults in any level of regular physical activity, showcasing psychiatric symptoms related to a disordered relationship with food, including depression and various eating disorders. The search on the literature databases was conducted on 20th October 2023 through multiple electronic databases (PubMed, SCOPUS, and Google Scholar) to capture as many relevant citations as possible. Exclusions were made for studies on children or psychiatric patients. The research was sourced from significant databases, emphasizing the correlation between dietary habits and mental health in athletes. Findings reveal that athletes, particularly in ultra-endurance and weight-dependent sports, are susceptible to psychiatric disorders such as depression, anxiety, and exercise addiction. Competitive bodybuilders also showed higher levels of depression and orthorexia nervosa symptoms. Tailored nutrition therapy, guided by healthcare professionals and adjusted to each athlete's specific needs and preferences, is crucial for addressing psychiatric symptoms and eating disorders in athletes. A holistic approach to recovery and well-being can significantly enhance both performance and overall quality of life, underscoring the importance of high-quality, balanced diets in supporting mental health and athletes' achievement.